Unmaking Malnutrition-Related Attritional Deaths In Covid-19 Regime: Does Digital Extension And Youth Nexus Count In Africa? - Okorie, V. O. (My University, 2022)
The implementation of COVID-19 pandemic regime has created barriers between extension agents and farm families as well as between input suppliers and farmers. Farm families that hitherto relied on faceto-face extension education to make crucial nutrition-related decisions and navigate Africa’s unstable food system are apparently constrained by lockdown and physical distancing arising from the pandemic regime. Malnutrition crises, including installment death from hunger, have besieged many households. Experts are, however, suggesting the nexus between youth and digital extension as a game changer in the quest to address Africa’s nutrition insecurity. This paper, therefore, uses thematic analysis of relevant data to assess potentials, possibilities and limits of this emerging nexus to alter the continent’s grim nutritional landscape. The paper argues that the nexus has the potential not only to overcome the pandemic-induced malnutrition challenges but also prepare the continent for the present and future pandemics.
Keywords: Covid-19; Digital Extension; Youth; Africa; Nutrition; Food Security